PEMBERDAYAAN KELOMPOK PKK DESA PULUTAN WETANKECAMATAN WURYANTORO KABUPATEN WONOGIRIMELALUI INTRODUKSI TEKNOLOGI PENGOLAHANKLOBOT JAGUNG - dan I.F.Bambang Sulistyono, Emi Widiyanti, Yayan Suherlan, (Universitas Negeri Yogyakarta, 2013)
AbstrakActivity in this program are to disseminate the use of cornhusk, totrain suvenir creation of cornhusk, to develop entrepreneurial motivation(Business Motivation Training), and to accompany in marketing andpioneered the establishment of a new business group.This event was attended by 30 participants PKK members PulutanWetan Village. The skill set include: preparation techniques cornhuskingredients, how to cultivate cornhusk become flowers for the table, flowersto decorate the tissue, making brooches and ornaments for the hairpin.In the process of mentoring has formed two new business groupsnamely